Efficacy of biocontrol agents with mancozeb against Cercospora leaf spot (Mycosphaerella cruenta) disease in cowpea - Megha, S; Tiwari, Shashi (Indian Journal of Plant Protection, 2025)
The present investigation was carried out with title Efficacy of biocontrol agents with mancozeb against Cercospora leaf spot (Mycosphaerella cruenta) disease in cowpea (Vigna unguiculata) at Central Research Field of Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj, during the kharif season of 2022 to evaluate the efficacy of combination of biocontrol agents with mancozeb on Cercospora leaf spot disease of cowpea. The experimental design used was Randomized Block Design replicated three times with 7 treatments which are mancozeb (1%), mancozeb (1%) + Bacillus subtilis (4%), mancozeb (1%) + Pseudomonas fluorescens (4%), mancozeb (1%) + Trichoderma harzianum (4%), mancozeb (1%) + Pseudomonas fluorescens (4%) + Bacillus subtilis (4%), mancozeb (1%) + Pseudomonas fluorescens (4%) + Trichoderma harzianum (4%), mancozeb (1%) + Bacillus subtilis (4%) + Trichoderma harzianum (4%) and control (untreated). The parameters assessed were plant height, number of pods per stand, pod length and disease intensity. The growth parameters were highest in cowpea treated with the biocontrol agents with fungicides particularly, mancozeb (1%) + Pseudomonas fluorescens (4%) + Trichoderma harzianum (4%) compared to other treatments of cowpea. Disease intensity were found to be significantly (P>0.05) lower in cowpea treated with the biocontrol agents with fungicides particularly, mancozeb (1%) + Pseudomonas fluorescens (4%) + Trichoderma harzianum (4%) and higher in treatment control (untreated) cowpea.